2017
DOI: 10.48550/arxiv.1706.03665
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Statistical properties of sketching algorithms

Abstract: Sketching is a probabilistic data compression technique that has been largely developed in the computer science community. Numerical operations on big datasets can be intolerably slow; sketching algorithms address this issue by generating a smaller surrogate dataset. Typically, inference proceeds on the compressed dataset. Sketching algorithms generally use random projections to compress the original dataset and this stochastic generation process makes them amenable to statistical analysis. We argue that the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…(D) puts restriction on the smallest eigenvalue of the matrix X n,ξ Xn,ξ /m n . Notably, Gaussian sketching approximately preserves the isometry condition (Ahfock et al, 2017), so that ∃ η 0 > 0 with the property that e min ( X n,ξ Xn,ξ /m n ) ≥ η 0 e min (X n,ξ X n,ξ /n) with probability f n depending on m n and p n . This, together with assumption A 1 (3) in Song and Liang (2017) is used to argue that assumption (D) is satisfied with a positive probability.…”
Section: Assumptions Framework and The Main Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…(D) puts restriction on the smallest eigenvalue of the matrix X n,ξ Xn,ξ /m n . Notably, Gaussian sketching approximately preserves the isometry condition (Ahfock et al, 2017), so that ∃ η 0 > 0 with the property that e min ( X n,ξ Xn,ξ /m n ) ≥ η 0 e min (X n,ξ X n,ξ /n) with probability f n depending on m n and p n . This, together with assumption A 1 (3) in Song and Liang (2017) is used to argue that assumption (D) is satisfied with a positive probability.…”
Section: Assumptions Framework and The Main Resultsmentioning
confidence: 99%
“…where the inequality in the fourth line follows from the fact that there exists η > 0 such that || Xn v|| 2 2 ≤ η||X n v|| 2 2 , for all v (Ahfock et al, 2017). This implies that e max ( X n Xn ) = sup…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This procedure can be performed by multiplying a given matrix by a random matrix from the right-hand or left-hand side. This is called random projection and it has been shown that this procedure preserves the Euclidean distance among the points approximately [78], [79]. To be precise, let us consider matrix X and target rank R In the first stage of the random projection approach, we generate a random matrix Ω = [ω 1 , ω 2 , .…”
mentioning
confidence: 99%